Projection of Ocean Wave Climate Change Based on Numerical Simulations - Zikra, Muhammad; Hashimoto, Noriaki; Mitsuyasu, Kodama (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
This study aims to analyze global wave climates of present and future time by using the WAM model. The analysis is performed based on wind climate data from the JMA/MRI-AGCM3.2 climate change projection. We analyze two 6-hourly wind data sets, covering two periods: the present climate ranging from 1979-2003 and future climate extending from 2075-2099. These wind data are used to implement the WAM model for producing the outputs of wave characteristics. Subsequently, the outputs from each period were used to study global wave climate in the future. The analysis showed that the wave climate is strongly dependent on the geographical position of regions from mid to high latitude and low latitude. This includes regions where the climate induced changes for present to future climate. The largest increases of significant wave height which reached approximately 5% occur in the southern parts of the Indian, Pacific and Atlantic Oceans and in the Antarctic Ocean. The decreases in the same magnitude around 5% occur especially in the North Atlantic Ocean.